PPAR-g агоністи: чи рішення про серцево-судинний ризик остаточне? - Кіхтяк, О. П. (Clinical Endocrinology and Endocrine Surgery, 2008)
Four month treatment with pioglitazone showed statistically relevant improvement of the certain list of markers: fasting glucose, HOMA-IR index, HbA1c. We speculate that descent of fasting glucose and C-peptide elevation may indicate peripheral improvement of insulin binding capacity since insulin concentration in blood circulation decreases. Treatment with pioglitazone showed its anti-atherosclerotic abilities by dyslipidemia improvement and by markedly decrease of the C-reactive protein, a strong predictor of cardiovascular events.